Extracorporeal Life Support. Issue 1 (January 2015) - Gray, Brian W.; Haft, Jonathan W.; Hirsch, Jennifer C.; Annich, Gail M.; Hirschl, Ronald B.; Bartlett, Robert H.
<x xml:space="preserve">Abstract</x> This is a review of the University of Michigan experience with extracorporeal life support (ECLS) also known as extracorporeal membrane oxygenation (ECMO). Two thousand patients were managed with ECMO from 1973 to 2010. The first 1, 000 patients were reported previously. Of the 2, 000 patients, 74% were weaned from ECLS, and 64% survived to hospital discharge. In patients with respiratory failure, survival to hospital discharge was 84% in 799 neonates, 76% in 239 children, and 50% in 353 adults. Survival in patients with cardiac failure was 45% in 361 children and 38% in 119 adults. ECLS during extracorporeal cardiopulmonary resuscitation was performed in 129 patients, with 41% surviving to discharge. Survival decreased from 74 to 55% between the first and second 1, 000 patients. The most common complication was bleeding at sites other than the head, with an incidence of 39%, and the least frequent complication was pump malfunction, with a 2% incidence. Intracranial bleeding or infarction occurred in 8% of patients, with a 43% survival rate. This is the largest series of ECLS at one institution reported in the world to date. Our experience has shown that ECLS saves lives of moribund patients with acute pulmonary and cardiac failure in all age groups.